Isolation and Analysis of Microplastics in Feather Clams (Anadara antiquata) at Tanjung Luar Fish Landing Base, East Lombok Regency - Aulia, Nurul Waroatul; Prasedya, Eka Sunarwidhi; Candri, Dining Aidil (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Microplastics are small particles <5 mm produced from plastic waste. The plastic waste thrown in the sea, As a result, microplastics have increased and are widespread almost throughout the sea surface, including Tanjung Luar Fish Landing and East Lombok Regency. Microplastics are very dangerous for human health due to microplastic contamination in feather clams, which are often consumed by the local community. Microplastics in the shellfish body can accumulate from the food chain and enter the digestive system. This study aims to determine the presence and characteristics of microplastics in feather clams (Anadara antiquata) at Tanjung Luar Fish Landing, East Lombok Regency. The research method used was descriptive quantitative. Samples of feather clams obtained from Tanjung Luar Fish Landing were separated from their shells. The clam meat was added with 10% KOH to destroy organic matter. The sample was incubated in a water bath until it was homogeneous. The sample was filtered using a 250 µm sieve. The filter results were dried with a dryer at 40˚C. Samples were identified with a microscope. The results showed microplastic contamination in feather clams from Tanjung Luar Fish Landing. Microplastic particles found were 59 particles with fibre types, as many as 47 particles, films 9 particles, and fragments 3 particles; there were 4 types of colours: black, clear, red and green. The dominant microplastics found were of the fibre type. Feather clams contaminated with microplastics harm human health, including metabolic disorders.